Applying social impact assessment (SIA) principles in assessing contribution of cultural heritage to social sustainability in rural landscapes. Issue 3 (5th August 2019) - Gallou, Eirini; Fouseki, Kalliopi
Abstract : Purpose: The purpose of this paper is to propose the use of social impact assessment (SIA) principles to evaluate the contribution of cultural heritage to social sustainability, supporting both a people-centered and socially responsible approach to heritage management. Design/methodology/approach: Specifically, the paper explores SIA as a methodological tool for post-project evaluation, used to define projects' contributions to aspects of social sustainability through analyzing impacts of participation in a rural context case study, that of the Scapa Flow landscape heritage scheme in Orkney Islands, Scotland, UK. Findings: Based on research findings from the thematic analysis of 40 semi-structured interviews on impacts (with heritage managers, planners and participants in the scheme), the paper proposes a combination of heritage value assessment process with social impact identification to achieve a context-relevant assessment of social sustainability. Existing research around social capital and sense of place supports the analysis of relevant impacts and heritage values. Findings support overlaps between socio-environmental impacts, when looking at the role of heritage for community well-being in rural contexts. Research limitations/implications: The qualitative approach allows for a context-relevant, bottom up impact assessment and allows for multiple stakeholders perceptions to be included. Practical implications: The proposed methodological approach has greater implications for the work of institutions and professionals involved in project evaluations that can inform participatory heritage project planning, ensuring high social relevance. Social implications: Application of SIA principles in heritage sector can increase social benefits of heritage projects and enable wider community participation in processes of heritage management. Originality/value: Through this case study, the effectiveness of SIA principles when applied in cultural heritage project evaluation is discussed, reflecting on a novel methodology for impact assessment in heritage.